Shwachman-Diamond syndrome: diagnosis, pathogenesis and prognosis. (3rd October 2017) - Valli, Roberto; Frattini, Annalisa; Minelli, Antonella
ABSTRACT: Introduction: Shwachman-Diamond Syndrome (SDS) is a rare autosomal recessive disease due to mutations in the SBDS and DNAJC21 genes, both involved in ribosome biogenesis. Patients affected by SDS show widely variable clinical features and have an increased risk to develop myelodysplastic syndrome, aplastic anemia and acute myeloid leukemia. Areas covered: Clinical features from diagnosis to surveillance and treatment of SDS patients are presented. It is mainly addressed the necessity to monitor the haematological and cytogenetic picture of the bone marrow in order to early identify any possible dysplastic/neoplastic sign to quickly treat the condition. Since, hematopoietic stem cell transplant is the only therapy for hematological complications, the useful preparative regimens is extensively discussed. In addition, recent molecular and cytogenetic studies are reported. Expert opinion: In our opinion, due to high variability of pathological phenotype presented by SDS patients, a prompt molecular diagnosis may help the management of the disease and may aim the cytological monitoring at bone marrow level, which could improve the surveillance of patients and, if necessary, carry to a prompt hematopoietic stem cell transplant.